Bacillus amyloliquefaciens G02 enhances selenium uptake in lettuce (Lactuca sativa) by improving soil selenium availability and rhizosphere microbiome regulation - Huang, Bingzhi; Li, Bei; Pan, Guofei; Huang, Danni; Yang, Guoming; Ma, Yanmin; Ya, Fengshuo; Rao, Mingliang; Wei, Yanyan (Frontiers in Microbiology, 2025)
Selenium (Se) is an essential trace element for human, but its low availability in soils results in its inadequacy in edible crops, thereby limiting its human intake. However, the role of the plant growth-promoting bacteria in soil Se availability and the pathways involved in biofortification in edible plants remain poorly understood. In this study, a Se-tolerant, plant growth-promoting bacterium, Bacillus amyloliquefaciens strain G02, which activates Se was isolated from the soils in Se-rich fields in Guangxi, China. We employed soil microcosm and potted experiments, along with metabolomics and 16S rRNA sequencing, to investigate how strain G02 incubation promotes elemental Se (0) solubilization, soil Se activation, and Se enrichment in lettuce. The strain G02 exhibited high phosphate solubilization (87.36 mg/L), IAA production (8.35 mg/L), as well as siderophore and ACC deaminase activities. Strain G02 is capable of dissolved Se(0) and Se minerals, increased pH, and secreted metabolites enhancing Se solubility. Soil microcosm experiments showed that the incubation of strain G02 increased available Se forms [soluble selenium (SOL-Se) and exchangeable selenium (EXC-Se)] in soil. Moreover, potted experiments revealed that the incubation of strain G02 increased biomass, Se concentration in lettuce, soil enzyme activities, beneficial microbial abundance and the native bacterial taxa. The strain G02 enhances soil Se availability through metabolites secretion, Se solubilization, and rhizosphere microbial regulation, improving ability of lettuce to absorb and transport Se. This study provides novel insights into the microbially mediated Se biofortification.